2022
DOI: 10.1371/journal.pbio.3001562
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 567,758 randomized controlled trials published over 30 years reveals trends in phrases used to discuss results that do not reach statistical significance

Abstract: The power of language to modify the reader’s perception of interpreting biomedical results cannot be underestimated. Misreporting and misinterpretation are pressing problems in randomized controlled trials (RCT) output. This may be partially related to the statistical significance paradigm used in clinical trials centered around a P value below 0.05 cutoff. Strict use of this P value may lead to strategies of clinical researchers to describe their clinical results with P values approaching but not reaching the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Additionally, Boutron et al observed that clinicians were more interested in reading the full text of articles with spin in their abstracts as compared with abstracts with no spin (P = .029). As Chiu et al pointed out, not only does spin affect clinical decision-making, but it also 22 examined .500,000 RCTs and found that .49,000 contained wording to try to express a statistical relationship even when one did not exist, a variant of type 3 spin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Boutron et al observed that clinicians were more interested in reading the full text of articles with spin in their abstracts as compared with abstracts with no spin (P = .029). As Chiu et al pointed out, not only does spin affect clinical decision-making, but it also 22 examined .500,000 RCTs and found that .49,000 contained wording to try to express a statistical relationship even when one did not exist, a variant of type 3 spin.…”
Section: Discussionmentioning
confidence: 99%
“…Data are presented as scatter plots with means ± SD. For all analyses, alpha was set to 5% and p < 0.09 considered as 'marginally significant' as per recent recommendations [25]. It is acknowledged that in the female cohort, low n's maybe a contributing factor for the observance of marginal significances rather than outright significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…As classical frequentist models are known for their inability to provide evidence in favor of the null hypothesis, we compared the logistic models of seizure outcome and major complications with and without the inclusion of surgery type by the Bayes factor (BF) 30 to assess the role of surgery type in explaining the seizure outcome. 31 Statistical significance was established at two-sided p-values of ≤.05. All statistical analyses were performed by RStudio (2022.02.3).…”
Section: Methodsmentioning
confidence: 99%